2020
DOI: 10.48550/arxiv.2008.00006
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Programmable Quantum Annealing Architectures with Ising Quantum Wires

Xingze Qiu,
Peter Zoller,
Xiaopeng Li

Abstract: Quantum annealing aims at solving optimization problems efficiently by preparing the ground state of an Ising spin-Hamiltonian quantum mechanically. A prerequisite of building a quantum annealer is the implementation of programmable long-range two-, three-or multi-spin Ising interactions. We discuss an architecture, where the required spin interactions are implemented via two-port, or in general multi-port quantum Ising wires connecting the spins of interest. This quantum annealing architecture of spins connec… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…These simulations successfully reproduce some behaviors in real-world many-body systems and provide insights into many-body dynamics, especially for nonequilibrium processes, which are much common in nature. Additionally, Rydberg many-body systems contribute to further research of problems in the quantum regime, such as optimization problems [64,65] and the self-verifying quantum variational simulation. [66] Despite many successful cases, in the future, Rydberg many-body systems need to increase scale to achieve simulations in large systems, and the maintaining time of the system needs to extend to allow the system evolves fully so that more many-body behaviors can be observed.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…These simulations successfully reproduce some behaviors in real-world many-body systems and provide insights into many-body dynamics, especially for nonequilibrium processes, which are much common in nature. Additionally, Rydberg many-body systems contribute to further research of problems in the quantum regime, such as optimization problems [64,65] and the self-verifying quantum variational simulation. [66] Despite many successful cases, in the future, Rydberg many-body systems need to increase scale to achieve simulations in large systems, and the maintaining time of the system needs to extend to allow the system evolves fully so that more many-body behaviors can be observed.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…Later on, by utilizing Rydberg-mediated four-body interaction, Glaetzle et al introduced a universal quantum annealer with allto-all couplings [159]. It is then found that anisotropy of the Rydberg interaction can also facilitate the construction of a different universal annealer [160]. Besides QAA, hybrid quantum-classical variational approaches such as quantum approximate optimization algorithms (QAOA) can also be implemented in Rydberg atom systems.…”
Section: E Near-term Applicationsmentioning
confidence: 99%
“…These are the largest programmable quantum information processors constructed to date, featuring thousands of superconducting flux qubits, and have driven much of the explosion of interest in QA in the last several years. Alternative superconducting approaches to QA with more coherent flux qubits are also being pursued, but have not yet approached similar scales [16][17][18][19][20], as is true for Rydberg atoms, which in theory feature high programmability and long-range connectivity [21,22]. Recently, the D-Wave processors were used as quantum simulators [23][24][25][26][27][28], thus joining gate-based approaches such as ion traps [29][30][31], quantum gas microscopes [32,33], Rydberg atoms [34][35][36], and transmon-based superconducting qubits [37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%